(untitled) (Fiep Bulletin - online, 2013)
Obesity can be conceived, a simplified way, as a condition accruement abnormal or excessive fat in the body, leading to a compromise of health (OMS,2004). In industrialized societies we can observe a lifestyle increasingly degenerate and the notorious interest more passive amusement instead of more vigorous physical activities, with physical effort, as well as by inadequate eating habits, creating these ideal conditions for the greater accumulation of fat and consequently the development of body weight. The Constitution of the Federal Republic of Brazil (1988) says that health is right and duty of the State, guaranteed through social and economic policies aimed at reducing the risk of disease and other diseases and universal access and equal to the actions and services for its promotion, protection and recovery. In this way one means of treating the matter of obesity, can and must be the school environment, being a public entity of the State, and is considered a social environment appropriate to treat knowledge for life, where future generations of society in development. The objective of this study was to identify in the PCN the knowledge to be treated in school that has direct relationship with obesity. As methodology was used the content analysis national curriculum parameters. We conclude that the PCN as an indispensable element for teachers of the school, in order to allowances and guidelines for able to address the issue of health with students and in particular stimulate postures healthy in the prevention of obesity from an early age.